A Versatile Model of Nonlinear Electrodynamic Loudspeaker Co-Operating with the Amplifier Designed by Way of Advanced Software - ERZA, Mehran; GAVIOT, Etienne; LEMARQUAND, Guy; TOURNIER, Pascal; CAMBERLEIN, Lionel; DURAND, Stephane; POLET, Frederic (Archives of Acoustics, 2014)
Sound processing with loudspeaker driving depends critically on high quality electroacoustic transducers together with their relevant amplifiers. In this paper, the nonlinear effects of electrodynamic loudspeakers are investigated as regard the influence of the changes of their main descriptive parameters values. Indeed, while being operated nonlinear effects observed with loudspeakers are due to changes of such constitutive parameters. Regarding either current or voltage-drive, an original model based on Simulink® is presented, taking account of all the electrical and mechanical properties closely associated with nonlinear behaviours. Moreover, as such a Simulink® model may be combined with the PSpice® advanced software, the behaviour of both loudspeaker and amplifier can be exhaustively investigated and optimized. To this end, the amplifier is simulated thanks to the Orcad-Capture-PSpice® software prior to match with the loudspeaker model with the so-called SLPS co-simulator. Then, values of the current flowing through the loudspeaker can be determined and plotted considering voltage controlling. Obviously in this case current-drive has not to be assessed.This way to proceed allows us to highlight any critical information especially due to the voice coil displacement, yielded velocity, and acceleration of the diaphragm. Indeed our approach testifies to the imperative necessity of mechanical measurements together with electrical ones. Then, considering a given amplifier-loudspeaker association with specific parameters changes of the latter, the entailed nonlinear distortion allows us to qualify and criticize the whole design. Such an original approach should be most valuable so as to match the best fitted amplifier with a given electrodynamic loudspeaker. Then non linear effects due to voltage and current-drive are compared highlighting the advantages of an apt current-controled policy.